SYNTHESIS, CHARACTERIZATION, AND APPLICATIONS OF ZNO–GRAPHENE NANOCOMPOSITES - Bhanu Priya, Sunita Bishnoi, Rupali Shrivastava (Chelonian Research Foundation, 2023)
The synthesis, characterisation, uses, and prospects for ZnO–Graphene nanocomposites in the future offer a constantly evolving field of scientific inquiry and technological advancement. This abstract highlight important elements that define the storey of these cutting-edge materials, thereby capturing the spirit of this complex journey. The production of ZnO–Graphene nanocomposites is characterised by an ongoing pursuit of accuracy and consistency. To accomplish successful integration, researchers have used a variety of synthetic processes, such as sol-gel methods and chemical vapour deposition. A primary goal is to optimise these techniques in order to guarantee consistency in the properties of the nanocomposites and improve scalability. The synthesis procedure is the cornerstone upon which ZnO–Graphene nanocomposites' special qualities and capabilities are constructed. When it comes to deciphering the complex structural features of ZnO–Graphene nanocomposites, characterization procedures are essential. Together, Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD) provide a thorough understanding of the composition, shape, and internal structure of the nanocomposites. Researchers find these techniques to be quite useful since they offer valuable insights that help fine-tune the properties of nanocomposite materials for certain applications. ZnO-Graphene nanocomposites have a wide range of applications, which demonstrate their adaptability and versatility. These nanocomposites have remarkable photocatalytic qualities that aid in the breakdown of contaminants in the air and water during environmental restoration. The special combination of graphene's conductivity and ZnO's semiconducting qualities makes for extremely sensitive and selective sensors in sensing technologies. The energy storage capacity of the nanocomposites is greatly increased, improving the efficiency of batteries and supercapacitors. They boost solar cell performance in photovoltaics, and their biocompatibility is utilised in biomedical applications for imaging and medication delivery. ZnO-Graphene nanocomposites have an exciting trajectory of innovation ahead of them. Scientists are ready to further refine synthesis techniques such that they are repeatable and scalable. At the forefront of research are improved nanocomposite qualities designed for particular uses. The next stage of these materials' evolution will be defined by innovative uses, integration with cutting-edge technologies, and a dedication to sustainable methods.